The Global Standards on Rehabilitation of Torture Survivors: From adoption to practice: from adoption to practice - Soley, Berta; Marboeuf, Hugo (Torture Journal, 2024)
This paper examines the implementation of the Global Standards on Rehabilitation (GSR) by members of the International Rehabilitation Council for Torture Victims (IRCT) and their impact on the quality of rehabilitation services provided to torture survivors. Methods: Qualitative and quantitative data were collected through surveys, post-training evaluations, and member feedback to assess the impact of the GSR on rehabilitation practices. Findings: Results show significant improvements, including more holistic rehabilitation, increased survivor participation, and stronger advocacy. Key challenges such as resource limitations, political barriers, and resistance to change were identified, alongside recommendations for future focus on survivor engagement, holistic support, and staff training. The paper concludes that the GSR roll-out has strengthened the capacity of IRCT members to provide quality rehabilitation services, highlighting the need for continued support and sustainable funding to expand impact.